If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12x + -3 = 22 + 2x Reorder the terms: -3 + 12x = 22 + 2x Solving -3 + 12x = 22 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. -3 + 12x + -2x = 22 + 2x + -2x Combine like terms: 12x + -2x = 10x -3 + 10x = 22 + 2x + -2x Combine like terms: 2x + -2x = 0 -3 + 10x = 22 + 0 -3 + 10x = 22 Add '3' to each side of the equation. -3 + 3 + 10x = 22 + 3 Combine like terms: -3 + 3 = 0 0 + 10x = 22 + 3 10x = 22 + 3 Combine like terms: 22 + 3 = 25 10x = 25 Divide each side by '10'. x = 2.5 Simplifying x = 2.5
| 4+2w=-6 | | Y=-4x^3+100x | | -6x+3(-4x-24)=-180 | | 2x-7+4x+14=49 | | D^2-10d+21=0 | | 6y-24=24x | | 3d+7=9 | | 35=5x+y | | 15-xy+5y-3x=0 | | w-7.14=5.74 | | k^2-6-16=0 | | 9ab-12a^2+6ab^2=0 | | 624.546=2*3.14*26.01+2*3.14*5.1*h | | 8=32b | | -1(p+5)=-3(2p-10) | | 625=25x | | 0.5(4x+7)=0.6-(x-3) | | 4.3x+25.8=64.5-8.6x | | 21a=7 | | 1/3x+2+1/2x-3=90 | | V=567 | | 3(x-4)-12+2x-9= | | 4.84x=2x | | (-3x-4)-(-2x-1)=6 | | 4(3x-5)+6=x | | 5g+14g+3= | | 4m-2=5m+7 | | 30x^2-85x+60=0 | | -2(5+6k)+16=-90 | | A^3-7a^2+6a-10= | | 4a+11-1a=2 | | 6x-4+2x-2=90 |